Hubungan Asupan Natrium, Kalsium dan Magnesium dengan Tekanan Darah pada Ibu Hamil Trimester II dan III (Studi di Wilayah Kerja Puskesmas Bulu Kabupaten Temanggung) - Ella Febriana; M. Zen Rahfiludin; Dina Rahayuning Pangestuti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Blood pressure is a force or a boost of blood to the artery’s wall when blood is pumped out of the heart to the body. Nutritional intake is related to blood pressure. There are some micronutrients which correlate with blood pressure such as sodium, calcium and magnesium. The purpose of this research was to analyze the correlation of sodium, calcium and magnesium intake with blood pressure in pregnant women second and third trimester in Bulu Health Center, Temanggung, Central Java. This was a quantitative analytical research with cross sectional design. Population of this research were all pregnant women in second and third trimester. Sampling technique was using purposive sampling. Data was collected using FFQ-Semi Quantitative forms and sphygmomanometer digital. It was analyzed using rank spearman trial. Result of this research showed that sodium, calcium and magnesium intake were low. There were no correlation of all the nutritional intake with pregnant women’s blood pressure in Bulu Health Center. This research recommended pregnant women to increase nutritional intake so that nutritional needsof the body and fetus can be fulfilled. Husband and family should take care of pregnant women’s nutritional intake. Health officers need to activate the socialization about balanced nutrition in pregnant women.